Pengaruh Pemberian Duckweed dan Virgin Coconut Oil (VCO) dalam Pakan terhadap Performa Produksi dan Daya Tetas Telur Ayam Cemani - Achmad Rofii; Tyas Rini Saraswati; Enny Yusuf Wachidah Yuniwarti (Politeknik Negeri Jember, 2018)
The aim of this study was to analyze the effect of using duckweed (Lemna minor) and virgin coconut oil (VCO) in diet on performance, hatchability, feed consumption, and body weight of cemani hen (Gallus gallus domesticus). Sixteen cemani hens were maintained from the age of 12 weeks to the first laying period and housed randomly in cages based on a completely randomized design (CRD) using four treatments and four replications. The treatment consisted: standard feed (T0), standard feed added 75% duckweed (T1), standard feed added 10 ml/kg VCO (T2), and standard feed added 75% duckweed and 10 ml/kg VCO (T3). The parameters were evaluated: age of maturity, egg number, fertility, hatchability, feed consumption, protein retention, and body weight. The results showed that feeding of duckweed and VCO had significant (P<0.05) effects on age of maturity, egg number, feed consumption, protein retention, and body weight, but there were no significant (P>0.05) effects on fertility, and hatchability of cemaniâ€™s hen. The feeding ofÂ duckweed 75% and VCO 10 ml/kg can be used as an alternative to improve performance and nutritional intake of cemaniâ€™s hen.